EFFECT OF GRADED LEVELS OF NPK ON GROWTH, YIELD AND QUALITY OF FINE RICE ( ALITY OF FINE RICE (Oryza sativa L.) Var. PUSA BASMATI 1121 - MEENAKSHI GUPTA; B. C. SHARMA; N. P. THAKUR; ARABDEEP KOUR; AJEEV BHARAT (The Bioscan, 2019)
An experiment was conducted to optimise NPK levels for higher yield and better quality of fine rice cultivar Pusa Basmati 1121. The experiment was laid out in split plot design with combination of three levels of P and two levels of K in main plots and four levels of N in sub plots. The results revealed that among different graded levels of N, P and K, application of nitrogen at 60 kg/ha though at par with nitrogen @ 50 kg/ha recorded significantly higher growth parameters, yield attributes, grain and straw yield than with 30 kg and 40 kg/ha of N in comparison. Grain and straw yield also followed similar trend i.e. grain yield of 42.21 and 44.24 q/ha was recorded during first and second year of experimentation, respectively. Also, maximum mean net returns (Rs. 53,327.6/ha), gross returns (Rs. 77,296.2/ha), and B:C (2.22) ratio was obtained with application of N @ 60 kg/ ha. Among P and K levels, maximum mean grain, (42.93 q/ha) straw yield (57.98 q/ha) and B:C (2.18) ratio though at par with others levels of P and K in comparison was recorded with application of phosphorus @ 35 kg/ ha and Potassium @15 kg/ha in conjunction.